2016
DOI: 10.1002/term.2136
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional polymer scaffolds for enhanced differentiation of human mesenchymal stem cells to hepatocyte-like cells: a comparative study

Abstract: Stem cell-based tissue engineering has emerged as a promising avenue for the treatment of liver diseases and as drug metabolism and toxicity models in drug discovery and development. The in vitro simulation of a micro-environmental niche for hepatic differentiation remains elusive, due to lack of information about crucial factors for the stem cell niche. For generation of functional hepatocytes, an in vivo three-dimensional (3D) micro-environment and architecture should be reproduced. Towards this, we fabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…9,31,41,46,51 Our finding that 3D biomaterials are potent modulators of endothelial specification concurs with Zhang et al that demonstrated a significant improvement of endothelial differentiation 3D fibrin (45% efficiency), compared to 2D (10% efficiency) substrates. 58 We believe this is the first report of endothelial differentiation of iPSCs within 3D synthetic polymer scaffolds.…”
Section: Discussionsupporting
confidence: 90%
“…9,31,41,46,51 Our finding that 3D biomaterials are potent modulators of endothelial specification concurs with Zhang et al that demonstrated a significant improvement of endothelial differentiation 3D fibrin (45% efficiency), compared to 2D (10% efficiency) substrates. 58 We believe this is the first report of endothelial differentiation of iPSCs within 3D synthetic polymer scaffolds.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, several gelatin-based scaffolds have been tailored to support hepatic tissues. [179][180][181] In an interesting study, a chitosan/gelatin composite scaffold with an organized microstructure analogous to the physiological hepatic tissue was shown to support the growth and proper development of hepatocytes in vitro. 182 This indicates that mimicking the topography of the native tissue is essential to generate scaffolds for tissue replacement.…”
Section: Gelatin-cell Composites For Cartilage and Bone Tissue Regenementioning
confidence: 99%
“…10 It is also used to replace defective body cells 82 and improve local tissue defects. 83 Cell therapies initially involved autologous bone marrow cell infusion, but methods for use of specific cells such as mesenchymal stem cells and macrophages have been developed.…”
Section: Use Of Tissue Specific Stem Cellsmentioning
confidence: 99%